Analisis Media Edukasi Puzzle Untuk Pendidikan Karakter Anak Usia Dini - Lisa Mardiana; Mutia Rahmi Pratiwi; Dzuha Hening (Expose: Jurnal Ilmu Komunikasi, 2021)
Early childhood character education is a crucial phase that requires serious attention. Media education is a solution in delivering messages related to early childhood character education. The purpose of this research is to analyze the puzzle media that has existed before so that it can be the basis for developing the puzzle media that will be designed by the author based on the development of children's self-concepts as part of character education. This research is a qualitative research with case study method. The resource persons who became the research subjects were two practitioners, namely child psychologists and practitioners of children's education media. The results show that puzzle educational media can be a solution for delivering character education to children and it is necessary to design educational media in the form of puzzles based on character education and the role of parents with the aim of developing self-esteem and self-confidence in it.